The IMF As a Biased Global Insurance Mechanism: Asymmetrical Moral Hazard, Reserve Accumulation, and Financial Crises. (5th November 2018) - Lipscy, Phillip Y.; Lee, Haillie Na-Kyung
Abstract: A large literature has established that the International Monetary Fund (IMF) is heavily politicized. We argue that this politicization has important consequences for international reserve accumulation and financial crises. The IMF generates moral hazard asymmetrically, reducing the expected costs of risky lending and policies for states that are politically influential vis-à-vis the institution. Using a panel data set covering 1980 to 2010, we show that proxies for political influence over the IMF are associated with outcomes indicative of moral hazard: lower international reserves and more frequent financial crises. We support our causal claims by applying the synthetic control method to Taiwan, which was expelled from the IMF in 1980. Consistent with our predictions, Taiwan's expulsion led to a sharp increase in precautionary international reserves and exceptionally conservative financial policies.